Feminism and christianity : questions and answers in the third wave - Riswold, Caryn D. (The Lutterworth Press, 2009)
Why should feminists care about Christianity? Why should Christians care about feminism? In Feminism and Christianity Riswold presents a collection of concise answers to basic questions like these in order to generate discussion about how the two can challenge each other and can even work together in the twenty-first century. Situated firmly in the third wave of feminist activism and scholarship as well as in contemporary Christian theology, Riswold addresses issues such as race, class, gender, and sexuality with an affirmation of tradition alongside a push for change. This book is an opportun.